Current Scenario of Poly (2, 5-Benzimidazole) (ABPBI) as Prospective PEM for Application in HT-PEMFC. (2nd April 2020) - Rath, Rosalin; Kumar, Piyush; Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, Sanjay K.
Abstract: In last two decades, acid doped polybenzimidazole as polymer electrolyte membrane (PEM) has been widely recognized and envisioned as "ideal" proton conducting materials for application in high temperature PEM fuel cell (HT-PEMFC). The majority of research and developmental work is mainly focused on poly (2, 2´-m-phenylene-5, 5´-bibenzimidazole), However, it is neither easy-processed nor inexpensive component of the respective family. On the other hand, among the various members belonging to benzimidazole family, poly (2, 5-benzimidazole) is unique because it possesses a cost-attractive, single-step synthesis process, high extent of doping as well as good chemical and thermal stability. In the recent years this material has proved its potency in the earlier research. Thus this review puts special emphasis on poly (2, 5-benzimidazole) and epitomizes the on-going breath-taking progress and achievements on the fabrication of poly (2, 5-benzimidazole) based membranes. The write-up describes the effect of blending, cross-linking, ionic liquids and incorporation organic/inorganic nano-fillers. In addition, incorporating other protonic dopants such as heteropoly acids into the chain of poly (2, 5-benzimidazole) molecular skeleton is also overviewed. Moreover, the critical interpretation of different causes responsible for earlier degradation and their effect towards the fabrication of high temperature membrane electrode assembly are visualized herein. Highlights: Current developments and existing challenges of ABPBI in PEMFC have been reviewed. PEM Modification and addition of protonic dopants has been discussed. Proton migration, permeability, stability and reliability are thoroughly illustrated. Different ABPBI-based membranes and their performance are comparatively analyzed. Graphical Abstract: